2012
DOI: 10.1007/s10753-012-9499-5
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-inflammatory Effect of Z-Ligustilide in Experimental Ovariectomized Osteopenic Rats

Abstract: The purpose of the present study was to investigate the anti-inflammatory activity of Z-Ligustilide (LIG) in experimental ovariectomized (OVX) osteopenic rats. The anti-inflammatory potential of LIG in the regulation of nuclear factor kappa B (NF-κB), maleic dialdehyde (MDA), polymorphonuclear cells (PMN), interleukin-1β (IL-1β), inducible nitric oxide synthase (iNOS) and tumor necrosis factor-α (TNF-α), adhesion molecule (ICAM-1) and cyclooxygenase-2 (COX-2) was determined by ELISA. LIG significantly inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…It has been demonstrated that oxidation-derived free radicals increase bone resorption by promoting osteoclastic differentiation [ 31 ]. Ma et al demonstrated that Z-ligustilide from the essential oil of A. sinensis inhibits the OVX-induced serum interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) levels [ 32 ]. IL-1β is known as a highly potent bone-resorptive cytokine [ 9 ] and TNF-α appears to synergize with IL-1 to increase bone resorption [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that oxidation-derived free radicals increase bone resorption by promoting osteoclastic differentiation [ 31 ]. Ma et al demonstrated that Z-ligustilide from the essential oil of A. sinensis inhibits the OVX-induced serum interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) levels [ 32 ]. IL-1β is known as a highly potent bone-resorptive cytokine [ 9 ] and TNF-α appears to synergize with IL-1 to increase bone resorption [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we do not find any reference that directly indicates the association between (Z)-Ligustilide and COX-1. There are relevant studies about the modulation of (Z)-Ligustilide on cyclooxygenase-2 (COX-2)272829, a protein that has similar function as COX-1. However, in our experiments of normal platelets, COX-2 is expected to be little expressed.…”
Section: Resultsmentioning
confidence: 99%
“…OVX rats, in the face of inflammatory challenges, express more iNOS than SHAM rats ( Crisafulli et al, 2009 ; Ma and Bai, 2012 ; Sakanashi et al, 2013 ; Hassouna et al, 2014 ), and estradiol is a known stimulator of NO synthesis, including the increase of iNOS expression and activity ( Nuedling et al, 1999 ; Zhu et al, 2002 ). In addition, progesterone is able to reduce iNOS activity in LPS-stimulated cells ( Su et al, 2007 ; Menzies et al, 2011 ), suggesting that the lower plasma levels of nitrite observed in the SHAM group may be the result of a synergism between iNOS inhibition by SMT and the reduction of the activity of this enzyme by circulating progesterone of these animals.…”
Section: Discussionmentioning
confidence: 99%